A comparison of shockwave dynamics in stochastic and periodic porous polymer architectures. (3rd January 2019) - Branch, Brittany; Ionita, Axinte; Patterson, Brian M.; Schmalzer, Andrew; Clements, Bradford; Mueller, Alexander; Dattelbaum, Dana M.
Abstract: Dynamic loading of materials is fundamental in understanding the mechanical response of cellular solids and elucidates time dependent properties that pertain to energy absorption under extreme conditions. Of particular interest is how the discrete behavior of the individual cell in a stochastic foam affects the dynamic shockwave behavior. The deformation mechanism in a stochastic open-cell foam is bending-dominated versus stretch-dominated in periodic lattice structures, resulting in a decrease in the plastic yield stress. Here, we investigate shockwave dynamics in stochastic open-cell foams through phase contrast imaging and finite element modeling. We observe that the distribution of pore sizes and the proximity of each produces a random topology with varying cell wall thicknesses that cause points of high strain creating irregularity in the shock wave at higher impact speeds. The shockwave dynamics of the stochastic foam are compared to periodic additive manufactured (AM) foams with similar density and it can be observed that modulation via microstructural control in elastomer foams has a dramatic effect on shockwave dynamics. Graphical abstract: Highlights: X-ray phase contrast imaging was employed to investigate deformation mechanisms of stochastic and additively manufactured polymer foams under shock loading. Compaction and localization phenomena were found to vary under shockwave compression due to local microstructures well above the elastic yield condition. Finite element modeling illustrates that stress behind the wavefront varies with compaction and densification of the non-uniform material density distribution.